2015
DOI: 10.1021/jp510972k
|View full text |Cite
|
Sign up to set email alerts
|

Stern-Gerlach Experiments on Fe@Sn12: Magnetic Response of a Jahn–Teller Distorted Endohedrally Doped Molecular Cage Cluster

Abstract: The magnetic response of the Fe@Sn 12 cluster is investigated by magnetic beam deflection experiments. In contrast to Mn@Sn 12 , the molecular beam of this cluster is deflected almost exclusively toward increasing field, also at low temperatures, supposable due to Jahn−Teller induced distortions of the tin cage. The magnitude of the magnetic dipole moment is extracted from the shift of the beam profile and provides evidence for a (partially quenched) contribution of electronic orbital angular momentum to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 23 publications
3
31
1
Order By: Relevance
“…[35][36][37][38][39][40][41][42] Thus, there is a plethora of captivating metal atom or ion encapsulated Si n -, Ge n -, Sn n and Pb 12 2-clusters that have been experimentally and theoretically examined. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] A few examples include kinetically stable noble gas atom or dimer (H 2 and He 2 ) encapsulated Pb 12 2and Sn 12 2clusters which have been predicted by our group. 59 Addressing the point of stability, it has additionally been shown that encapsulated Pb 12 2and Sn 12 2clusters preserved their structural integrity even at high temperatures of 700 K. 59 Delving further, considering their similar cage sizes, the possibility of having an Lr@C 60 cluster 60 makes the prediction of Lr or Lu encapsulated Pb 12 2and Sn 12 2clusters realisable.…”
Section: Choosing Encapsulated Clusters Of Tin and Lead As Model Systemsmentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42] Thus, there is a plethora of captivating metal atom or ion encapsulated Si n -, Ge n -, Sn n and Pb 12 2-clusters that have been experimentally and theoretically examined. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] A few examples include kinetically stable noble gas atom or dimer (H 2 and He 2 ) encapsulated Pb 12 2and Sn 12 2clusters which have been predicted by our group. 59 Addressing the point of stability, it has additionally been shown that encapsulated Pb 12 2and Sn 12 2clusters preserved their structural integrity even at high temperatures of 700 K. 59 Delving further, considering their similar cage sizes, the possibility of having an Lr@C 60 cluster 60 makes the prediction of Lr or Lu encapsulated Pb 12 2and Sn 12 2clusters realisable.…”
Section: Choosing Encapsulated Clusters Of Tin and Lead As Model Systemsmentioning
confidence: 99%
“…To achieve magnetic superatoms, a singely magnetic TM atom were embedded into a small simple-metal cluster, because either the D-state (magnetic state) of superatoms almost exclusively comes from atomic d-state (that is, for the filling superatomic shells, atomic d electrons are thought as delocalized valence electrons) or its superatomic D-state (magnetic state) hybridize strongly with atomic d-states (that is, atomic d electrons are strongly localized and not fill superatomic shells) in previous reports. 6,9,10,12,13,[29][30][31][32][33][34][35] The exchange-splitting between the majority of superatomic D shells (atomic d shells) and their minority states can resulted in by both cases of above, so a superatom can have a corresponding spin magnetic moment. However, the spin magnetic moment of one superatom may be very vulnerable to its surrounding environments, which restricts the practical applications of superatoms.…”
Section: Magnetic Analysis and Roles Of Tm's (M's) D Valence Electmentioning
confidence: 99%
“…During the last few decades, copper clusters have been demonstrated to have similar catalytic activities with those of gold clusters for the low temperature CO oxidation and partial oxidation of hydrocarbons 1 2 3 4 5 6 . At the same time, theoretical and experimental work has also shown that the nature of small clusters can be considerably modified by the addition of impurity atom(s) 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 . Copper clusters doped with different transition-metal atoms have been expected to tailor the desired catalytic, electronic, magnetic and optical properties for potential applications in solid state chemistry, microelectronics, nanotechnology and materials science 40 41 42 43 44 45 46 47 48 49 50 .…”
mentioning
confidence: 99%